1995
DOI: 10.1111/j.2044-8309.1995.tb01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Mindless processing of requests? Don't ask twice

Abstract: This study examines the mindlessness hypothesis and its associated compliance-gaining paradigm from the perspective of politeness theory. The main prediction of politeness theory, which is not taken into account in the mindlessness literature, is that the perceived magnitude of an imposition is a function not only of the size of favour asked but also of the framing of the request itself. A confederate asked students studying in the library for either one or 10 sheets of paper using appropriate variations of La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…However, we propose that sometimes the sheer presence of an explanation is enough for people to accept power differences. Past research has shown that people tend to accept even weak or placebic explanations for negative outcomes (e.g., Haines & Jost, 2000;Kappen & Branscombe, 2001;Langer, Blank, & Chanowitz, 1978;Slugoski, 1995). In one of Langer and colleagues' classic studies, a person about to use a copying machine was asked to let someone else use it first.…”
Section: Effects Of Power Explanations On the Powerful And The Powerlessmentioning
confidence: 99%
“…However, we propose that sometimes the sheer presence of an explanation is enough for people to accept power differences. Past research has shown that people tend to accept even weak or placebic explanations for negative outcomes (e.g., Haines & Jost, 2000;Kappen & Branscombe, 2001;Langer, Blank, & Chanowitz, 1978;Slugoski, 1995). In one of Langer and colleagues' classic studies, a person about to use a copying machine was asked to let someone else use it first.…”
Section: Effects Of Power Explanations On the Powerful And The Powerlessmentioning
confidence: 99%
“…The participants clearly judged that such replies conveyed an indirect, face-threatening meaning for the speaker. Furthermore, when this interpretation was canceled by the context (e.g., the participants were explicitly informed that the presentation had been excellent), the participants found the replies much more ambiguous and difficult to understand (see also Holtgraves, 1999;Holtgraves & Yang, 1990, 1992Slugoski, 1995).…”
Section: Virginie Demeure Jean-françois Bonnefon and éRic Rau R R Fmentioning
confidence: 99%
“…Conversely, a reason that includes seemingly explanatory information for a negative outcome may attenuate anger, feelings of injustice and illegitimacy. Research suggests that when people are provided with an explanation, they experience less imposition than when they are not provided with an explanation (Slugoski, 1995). Similarly, people who perceived that they were included in a decision process reported feeling that they had received fair treatment to a greater degree than those without 'voice' (Lind, Kanfer, & Early, 1990).…”
mentioning
confidence: 99%